2002
DOI: 10.1051/0004-6361:20020599
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed radiation from neutron star winds

Abstract: Abstract. The radiation of a pulsar wind is computed assuming that at roughly 10 to 100 light cylinder radii from the star, magnetic energy is dissipated into particle energy. The synchrotron emission of heated particles appears periodic, with, in general, both a pulse and an interpulse. The predicted spacing agrees well with the Crab and Vela pulse profiles. Using parameters appropriate for the Crab pulsar (magnetisation parameter at the light cylinder σL = 6× 10 4 , Lorentz factor Γ = 250) agreement is found… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 23 publications
4
97
2
Order By: Relevance
“…In the latter case extracting the pulsed component from the total data would be misleading. Possibly the wind model by Kirk et al (2002) offers an example for a source of radiation which produces fixed position angle at all phases except from those at which the peaks occur. In the model, high-energy radiation is emitted at large distances from the star (10−100R lc ) at current sheets, which separate "layers" of the toroidal magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case extracting the pulsed component from the total data would be misleading. Possibly the wind model by Kirk et al (2002) offers an example for a source of radiation which produces fixed position angle at all phases except from those at which the peaks occur. In the model, high-energy radiation is emitted at large distances from the star (10−100R lc ) at current sheets, which separate "layers" of the toroidal magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Explaining pulsation by such a mechanism was already suggested at the beginning era of pulsar theory as proposed by Michel (1971) and . These ideas have been reinvestigated more recently by Kirk et al (2002). These studies showed that the striped wind is a possible site for generation of incoherent high-energy radiation, going from optical up to gamma rays.…”
Section: J Pétrimentioning
confidence: 99%
“…We use an explicit asymptotic solution for the large-scale field structure related to the oblique split monopole and valid for the case of an ultrarelativistic plasma (Bogovalov 1999). Due to relativistic beaming effects, it has already been shown that this model gives rise to pulsed emission (Kirk et al 2002) and can satisfactorily fit the optical polarization data from, for instance, the Crab pulsar (Pétri & Kirk 2005).…”
Section: Introductionmentioning
confidence: 82%